Mitosfera do consumo: trajetos do sentido e narrativas mediáticas - Oliveira, Frederico Jorge Tavares de (2018)
The Mitosphere of Consumption is a theoretical notion developed in the large area of Communication Sciences; it is particularly linked to studies of communication and consumption and to studies of the imaginary. Along with the trajectories of meaning and media narratives is a notion that serves to understand the short-circuits of the imaginary, processes of flow and reflux of symbolic images in the practices of communication and consumption. Faced with a consummation of media narratives (what was called the media consummation), this work identifies the formation of symbolic images of consumption. The Mitosphere of Consumption, coupled with a series of differentiated and articulated notions, was treated in this research in two parts. In the first one, it was deciphered what gives the title of the thesis: “Mitosphere of Consumption: trajectories of meaning and media narratives”, accentuating issues of epistemological, theoretical and methodological order; in the second part, we described its force of affectation, or else a hermeneutic force and the revelation of the symbolic images from tragedies and narratives that involved soap opera actors and a soccer team (what was called the media tragedies). The choice of these events occurred according to their own emergence and visibility in the public and media sphere, and also because it was possible to indulge in their affective and symbolic dynamics. The study of these media tragedies occurs in a singular combination of techné and arché, between the new and the archaic, and reveals certain aspects of reality – the deepest ones – that defy any form of knowledge. Studying the sphere of myth, tragedy and the meanings of death with the media narratives may, however, be a key to understanding how a consumer society says and organizes itself from symbolic images; or how the present embodies what is substantial. Undoubtedly, a rapprochement with popular wisdom, with daily life, was held here, which seemed to us adequate to a diagnosis of how some sensitive atmospheres of communication, consumption and imaginary are formed. Its prognosis will be another matter.